Evaluation of clinical performance and safety for the rechargeable InterStim Micro device in overactive bladder subjects: 6‐month results from the global postmarket ELITE study. Issue 4 (14th March 2023) - Goudelocke, Colin; Xavier, Keith; Pecha, Barry; Burgess, Kimberly; Perrouin‐Verbe, Marie‐A.; Krlin, Ryan; Michaels, Jodi; Shah, Sagar; Peyronnet, Benoît; Zaslau, Stanley; Champs, Mylène; Papi, Bianca; et al.
Abstract: Aims: Sacral neuromodulation (SNM) is an advanced therapy option for the treatment of overactive bladder (OAB), nonobstructive urinary retention, and fecal incontinence. The aim of this ongoing prospective, multicenter, global, postmarket study is to confirm safety and clinical performance of the InterStim TM Micro system for SNM in all indications. Reported here are the results for the OAB cohort through 6‐month follow‐up. Methods: Eligible OAB subjects that had a successful therapy evaluation were enrolled after implant of an InterStim Micro implantable pulse generator (IPG). Subjects completed voiding diaries and the Overactive Bladder Quality of Life questionnaire (OAB‐q) at baseline and follow‐up visits occurring at 3 months and 6 months postimplant. Safety was evaluated as device‐, procedure‐, or therapy‐related adverse events. The primary objective for the OAB cohort was to demonstrate an improvement in OAB‐q Health Related Quality of Life (HRQL) total score at 3 months postimplant compared to baseline. Results: Sixty‐eight OAB subjects were enrolled and implanted with an InterStim Micro IPG. Of those, 67 and 66 subjects completed the 3‐ and 6‐month follow‐up visits, respectively. The OAB‐q HRQL demonstrated a statistically significant improvement from baseline to 3‐month follow‐up with an average increase of 33 ± 24 points ( n = 67, p < 0.001). The change was also observed at 6‐months with an average increase of 31 ± 23 points ( n = 65) compared to baseline. Eighty‐two percent of subjects achieved the minimally important difference in HRQL score at 3‐ and 6‐month, respectively, with a change of 10 points or greater. The majority of subjects reported that their bladder condition was better at 3‐month (92.5%, 62/67) and 6‐month (89%, 59/66) compared to before they were treated with SNM therapy delivered by the InterStim Micro system. For subjects with urgency urinary incontinence (UUI), the average change from baseline to follow‐up in UUI episodes/day was −3.6 (95% CI: −4.7, −2.6; n = 62) at 3‐month and −3.7 (95% CI: −4.7, −2.7; n = 61) at 6‐month. Among subjects with urgency‐frequency (UF), the average change from baseline to follow up in voids/day was −4.5 (95% CI: −6.3, −2.7; n = 52) at 3‐months and −4.4 (95% CI: −6.0, −2.7; n = 52) at 6‐month. The cumulative incidence of device‐, procedure‐, or therapy‐ related adverse events was 7.4% (5/68). Out of these five related adverse events, there was one serious adverse event (1.5%, implant site pain) at the time of database snapshot. Conclusions: These data confirm the safety and clinical performance of the InterStim Micro device for subjects with OAB by demonstrating a significant improvement in OAB‐q HRQL score at 3‐month. Similar improvements were observed at 6 months in addition to an incidence of adverse events that is comparable to previously reported rates for SNM.